Penerapan Metode Analytical Hierarchy Process (AHP) dalam Perekrutan Petugas Keamanan - Yustria Handika Siregar; Muhammad Dedi Irawan; Agung Hazarin Aulia Chaniago (Jurnal Informatika Universitas Pamulang, 2020)
The security category does not escape a strict security system. The Security Task Force (SATGASKAM) is a unit that guards every agency and company in order to avoid crime. There were several problems in the security unit recruitment process. This applies a conventional assessment. It is said to be conventional because the assessment system in the recruitment only involves human reasoning abilities from a number of predetermined criteria. In this study, the Analytical Hierarchy Process (AHP) method was applied for the security guard recruitment system. The selection process uses criteria which are the requirements for being accepted as security officers. The criteria used are the level of education, the equality value, the psychological score, and the results of the interviews. These criteria include the requirements contained in the regulation of the Head of Police of the Republic of Indonesia. The research method is carried out in several stages by comparing the AHP calculation process and the process of the result value of the system. The AHP process begins by determining the criteria, the eigenvalues. The results of the AHP method show transparency in recruitment with respective values and have a certain weight according to the priority of the agency.